Кальницький козацький полк в Національно-визвольній війні 1648–1657 рр. - Казьмирчук, Г.; Казьмирчук, М. (Краєзнавство, 2019)
У статті аналізується діяльність та висвітлюється формування, кількісний склад та бойовий шлях Кальницького козацького полку періоду Національно-визвольної війни 1648–1657 рр., що тісно пов'язано з історією нинішнього села Кальника. Спираючись на архівні та опубліковані джерела, спростовуються міфи та встановлюється історична правда щодо функціонування Кальницького козацького полку, який, безперечно, відіграв важливу роль у військових кампаніях, політичних перипетіях та державотворчих процесах за часів гетьманування Богдана Хмельницького. The article analyzes the activity and highlights the formation, quantitative composition and combat path of the Kalnitsky Cossack Regiment during the period of the War of National Liberation 1648–1657, which is closely connected with the history of the current Kalnik village. Based on archival and published sources, myths are refuted and historical truth about the functioning of the Kalnycky Cossack Regiment, which undoubtedly played an important role in military campaigns, political peripetias and state-building processes during Hetman Bohdan Khmelnytsky, is established. The military events of the National Liberation War led to the creation of Cossack regiments – one of the most important organizational forms of military confrontation with the forces of the Commonwealth, which wished peace and tranquility among the rebellious Ukrainian people for noble people. According to the «Register of the Zaporozhian Army in 1649», 2050 Cossacks were registered in the Kalinitsky Cossack Regiment. The most glorious were the Kalnyk colonels Ivan Bogun, Ivan Sirko and Ostap Gogol. Kalnitsky regiment during the Khmelnytskyi era has undergone a difficult path of formation and development. The Cossacks of the Kalnitic Regiment participated in all major military battles. It is possible to say that the regiment was formed spontaneously, related to the activities of the first colonel - Ostaf Gogol (1648 - the first half of 1649). The Kalnitsky regiment was involved in Ukrainian-Moldovan relations in 1653. B. Khmelnitsky, in an effort to expand the composition of the anti-Polish coalition, decided to bring the Moldovan host to an alliance, marrying his own son with the daughter of the Voivode of Moldavia Vasily Lupu. About the participation of the Kalinitsky regiment in the National Liberation War events of 1648, nothing definitely is known. It can be assumed that when the Ukrainian people fought with the Crown Army under the Yellow Waters and Korsun, the regiment was only formed. The regiment participated in battles under Zbarazh, Zborov, Berestechko and in other battles.